Effect of impact load on the tubular steel members of offshore structures - 381978 Azliza Abdullah (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2005